The The Impact of Behavioral Aspects on Investment Decision Making - Ninditya Nareswari; Alifia Salsabila Balqista; Nugroho Priyo Negoro (Jurnal Manajemen dan Keuangan, 2021)
This study aims to investigate the impact of behavioral aspects (sentiment investor, overconfidence, salience, overreaction, and herd behavior) on investment decision making. The sample contained 413 individual investors—used partial least square structural equation modeling (PLS-SEM) as a data analysis technique. The results showed that sentiment investors, overconfidence, salience, overreaction, and herd behavior positively affect investment decision making. The finding of this study has important implications for the investor to understand themselves to anticipate bias in investment decision making.